E-content development: Indian initiatives / Dr. S. Senthilnathan - Senthilnathan, S. (Dr.) (Penerbit UiTM (UiTM Press), 2009)
Ever since the buzz letter 'e' got tagged to the word 'learning', the world of education has witnessed a plethora of ICT initiatives with varying degrees of success. Thanks to the far-sighted approach that India followed in the field of Information Technology, world's best information technologists are available in the country and state-of-the-art facilities in terms of technologies and infrastructure, comparable with the most advanced countries are available to Indian teachers and students. E-content development is a major task before the teachers and content developers and the need for the same is more pronounced in India to provide quality education to 8.8 million students in 348 universities and 17,695 colleges across the country. In this regard, the Indian subcontinent has witnessed a considerable number of efforts to create e-content as well as to build the capacity of the teaching community for content creation. The most important ones are the efforts of the Consortium for Educational Communication of the University Grants Commission through the 17 Educational Multimedia Research Centres and the National Programme on Technology Enabled Learning through the Indian Institutes of Technology. This paper attempts to provide an account of these initiatives against the backdrop of India's fast expanding IT infrastructure and the current e-readiness.